Legal aspects of economic integration in Africa - Oppong, Richard Frimpong, 1978- (Cambridge : Cambridge University Press, 2011)
'Richard Frimpong Oppong challenges the view that effective economic integration in Africa is hindered by purely socio-economic, political and infrastructural problems. Inspired by the comparative experiences of other regional economic communities and imbued with insights from constitutional, public and private international law, it argues that even if the socio-economic, political and infrastructural challenges were to disappear, the state of existing laws would hinder any progress. Using a relational framework as the fulcrum of analyses, it demonstrates that in Africa's economic integration processes, community-state, inter-state and inter-community legal relations have neither been carefully thought through nor situated on a solid legal framework, and that attempts made to provide legal framework have been incomplete and, sometimes, grounded on questionable assumptions. To overcome these problems and aid the economic integration agenda that is essential for Africa's long-term economic growth and development, concrete proposals for radical reforms to community and national laws are made'--
Machine generated contents note: Introduction; 1. Africa's economic integration - an introductory overview; 2. Legal framework for managing relational issues; 3. The AU, AEC and regional economic communities; 4. Community-state relations in Africa's economic integration; 5. Relational issues before the community courts; 6. AU/AEC institutions and the enforcement of community law; 7. Implementing community law in African states; 8. Inter-institutional relations: public-private international law dimensions; 9. Interstate relations, economic transactions and private international law; 10. Conclusion.
Includes bibliographical references (pages 320-345) and index.
Keywords: Africa -- Economic integration